Unconstrained Melting And Solidification Inside Rectangular Enclosure - Rabinataj Darzi, A. A.; Hassanzadeh Afrouzi, H.; Khaki, M.; Abbasi, M. (University of Eloued جامعة الوادي, 2015)
The present study concerns with the numerical study of unconstrained solidification and melting of phase change material (PCM) inside a two dimensional open rectangular cavity. The Cavity is filled by RT-27 as phase change material and air. Numerical study is carried out for different cavity aspect ratios. Result indicates that the conduction heat transfer is dominant at initial time of melting process where the layer of liquid PCM near hot surface is so thin. Solid PCM sinks to bottom of cavity due to higher density in respect to liquid PCM. Melting rate does not experience significant change by increasing cavity aspect ratio. The time of full solidification is much more than melting. It is due to the absence of natural convection with respect to melting process. By increasing the cavity aspect ratio, the solidification rates enhances significantly and its total time therefore reduces.
Articale in Journal of fundamental and Applied Sciences Vol. 07, N. 03
Keywords: Phase change material; melting; solidification; rectangular cavity.